Evaluation of magnetic matrix solid‐phase dispersion for the determination of polychlorinated biphenyls in water samples by gas chromatography with electron capture detection. Issue 10 (28th April 2016) - Diao, Chun‐peng; Yu, Xiaoting; Li, Cong; Yang, Xiao; Sun, Aling; Liu, Renmin
Abstract : A vortex‐assisted magnetic matrix solid‐phase dispersion method was proposed for the determination of polychlorinated biphenyls in different matrix water samples by gas chromatography with electron capture detection. Magnetic bamboo charcoal (MBC) was synthesized for the adsorption of polychlorinated biphenyls in water samples. Complete separation of the liquid phase and the solid magnetic bamboo charcoal was easily achieved by using a permanent magnet. Under the optimized conditions, good linearity in the range of 0.006–5.0 μg/L was obtained with regression coefficients ( r ) higher than 0.9986. Based on a signal‐to‐noise ratio of 3, limits of detection were found to be 0.001–0.003 μg/L. Relative standard deviations ranged from 2.92 to 6.56%. Relative recoveries were 96.6–111.2% for the spiked wastewater sample and 90.7–104.7% for the spiked lake water sample. All results showed that the proposed method was simple, sensitive, and reliable for the determination of polychlorinated biphenyls in water samples.